Relações entre vaidade, comparação social e conspicuidade: uma análise da predisposição ao consumo de viagens de turismo - Carvalho, Anderson Romário Torres (2021)
This study aimed to analyze the influence of vanity and social comparison, taking into account envy and the use of social networks, on the conspicuous consumption of tourism. For this, a bibliographic review was carried out, supporting the theoretical relationships and resulting in the elaboration of 5 hypotheses to be tested in the proposed model. It is a quantitative and descriptive research carried out through a survey, which involved the elaboration of a structured questionnaire composed of items from the validated scales of the constructs, which underwent an adaptation to the context of the study. The collected data were analyzed based on an initial descriptive exploratory analysis, followed by an exploratory factor analysis (AFE), multivariate analysis techniques, processed in the SPSS software, and structural equation modeling (MEE) using the AMOS software, in the in order to verify the hypotheses of the study. The main results are that there is a positive relationship between the social comparison and online social comparison of consumers of tourism trips, between the social comparison and the vanity of these consumers, the social comparison and vanity are predictors of conspicuous consumption of travel, vanity being the aspect that has the greatest influence, especially when related to envy and online social comparisons, and the conspicuous consumption of these consumers positively and strongly influences the predisposition to the consumption of tourism trips. Thus, the study contributes to the understanding of the consumption behavior of consumers of tourism trips.